7
$\begingroup$

How to prove $ \int_0^\infty e^{-x^2} \; dx = \frac{\sqrt{\pi}}2$ other than changing into polar coordinates? It is possible to prove it using infinite series?

$\endgroup$
12
$\begingroup$

Method 1. Let $I$ denote the integral. Then for $s > 0$, the substitution $t = x\sqrt{s}$ gives

$$ \int_{0}^{\infty} e^{-sx^2} \; dx = \frac{1}{\sqrt{s}} \int_{0}^{\infty} e^{-t^2} \; dt = \frac{I}{\sqrt{s}}. $$

Thus for $u = x^2$,

$$\begin{align*}I^2 &= \int_{0}^{\infty} I e^{-x^2} \; dx = \int_{0}^{\infty} \frac{I}{2\sqrt{u}}e^{-u} \; du = \int_{0}^{\infty} \frac{1}{2}e^{-u}\int_{0}^{\infty}e^{-ut^2}\;dtdu\\ &= \int_{0}^{\infty}\int_{0}^{\infty} \frac{1}{2}e^{-u}e^{-ut^2}\;dudt = \int_{0}^{\infty}\frac{1}{2(t^2+1)}\;dt = \frac{\pi}{4}, \end{align*}$$

which proves the desired result. Note that this is in fact equivalent to the proof in Wikipedia.

Method 2. We assume that we are aware of the Wallis product

$$ \prod_{n=1}^{\infty} \left(\frac{2n}{2n-1} \cdot \frac{2n}{2n+1}\right) = \frac{2}{1} \cdot \frac{2}{3} \cdot \frac{4}{3} \cdot \frac{4}{5} \cdot \frac{6}{5} \cdot \frac{6}{7} \cdot \frac{8}{7} \cdot \frac{8}{9} \cdots = \frac{\pi}{2}. $$

Now, it is not hard to find that

$$ f_n(x) = \begin{cases} \left(1 - \tfrac{x^2}{n}\right)^{n} & 0 \leq x \leq \sqrt{n} \\ 0 & \text{otherwise}. \end{cases} $$

increases to $e^{-x^2}$. (Simple application of Bernoulli's inequality will suffice.) Then by monotone convergence theorem,

$$ I := \int_{0}^{\infty} e^{-x^2} \; dx = \lim_{n\to\infty} \int_{0}^{\sqrt{n}} \left(1 - \frac{x^2}{n}\right)^{n} \; dx = \lim_{n\to\infty} \sqrt{n} \int_{0}^{\frac{\pi}{2}} \sin^{2n+1}\theta \; d\theta, $$

where we have used the substitution $x = \sqrt{n}\,\cos\theta$. Now let

$$I_n = \int_{0}^{\frac{\pi}{2}} \sin^{2n+1}\theta \; d\theta. $$

Then for $n \geq 1$,

$$\begin{align*}I_n &= \left[\sin^{2n}\theta (-\cos\theta)\right]_{0}^{\frac{\pi}{2}} - \int_{0}^{\frac{\pi}{2}} 2n \sin^{2n-1}\theta \cos\theta (-\cos\theta) \; d\theta \\ &= \int_{0}^{\frac{\pi}{2}} 2n \sin^{2n-1}\theta (1-\sin^2 \theta) \; d\theta = 2n(I_{n-1} - I_n) \end{align*}$$

and we have $I_0 = 1$ and $I_n = \frac{2n}{2n+1} I_{n-1}$. Thus

$$ I_n = \prod_{k=1}^{n} \frac{2k}{2k+1}. $$

Therefore, by Wallis product,

$$ I^2 = \lim_{n\to\infty} n \prod_{k=1}^{n} \left( \frac{2k}{2k+1} \cdot \frac{2k}{2k+1} \right) = \lim_{n\to\infty} \frac{n}{2n+1} \prod_{k=1}^{n} \left( \frac{2k}{2k-1} \cdot \frac{2k}{2k+1} \right) = \frac{1}{2} \cdot \frac{\pi}{2} $$

and we have the desired result. (Conversely, knowing $I$, it can be used to prove the Wallis product formula.)

$\endgroup$
  • 2
    $\begingroup$ Method I is really the polar method.. $\endgroup$ – nbubis Aug 29 '12 at 9:15
6
$\begingroup$

Because $x \mapsto e^x$ is convex, $\displaystyle \left( 1- \frac{u}{n} \right)^n \leq e^{-u} \leq \left( 1+ \frac{u}{n} \right)^{-n}$, so $\displaystyle \int_0^{\sqrt{n}} \left( 1- \frac{x^2}{n} \right)^n dx \leq \int_0^{\sqrt{n}} e^{-x^2} dx \leq \int_0^{\sqrt{n}} \left( 1+ \frac{x^2}{n} \right)^{-n} dx$.

We use the change of variables $x= \sqrt{n} \sin(\theta)$: $\displaystyle \int_0^{\sqrt{n}} \left( 1- \frac{x^2}{n} \right)^n dx = \int_0^{\pi/2} \cos^{2n+1} (\theta) d\theta= \sqrt{n} W_{2n+1}$, where $W_{2n+1}$ is a Wallis integral.

If $p \geq \sqrt{n}$, $\displaystyle \int_0^{\sqrt{n}} \left(1+ \frac{x^2}{n} \right)^{-n} dx \geq \int_0^p \left(1+ \frac{x^2}{n} \right)^{-n} dx$. We use the change of variables $x=\sqrt{n} \tan (\theta)$ to find: $\displaystyle \int_0^{\arctan(p)} \sqrt{n} \cos^{2n+2} (\theta) d \theta \underset{p \to + \infty}{\longrightarrow} \sqrt{n} W_{2n+2}$.

Finally, $\displaystyle \sqrt{n} W_{2n+1} \leq \int_0^{\sqrt{n}} e^{-x^2}dx \leq \sqrt{n} W_{2n+2}$. But $\displaystyle W_n \underset{n \to + \infty}{\sim} \sqrt{\frac{\pi}{2n}}$ so $\displaystyle \int_0^{+ \infty} e^{-x^2}dx= \frac{\sqrt{\pi}}{2}$.

With this method, an asymptotic development of $W_n$ gives an asymptotic development of the integral.

$\endgroup$
3
$\begingroup$

$$ \int_{-\infty} ^\infty e^{-x^2} \; dx =I$$
$$ \int_{-\infty}^\infty e^{-y^2} \; dx =I$$
$$\int_{-\infty}^\infty e^{-x^2}\times e^{-y^2} \; dx =I^2$$
$$\int_{-\infty}^\infty e^{-(x^2+y^2)}\; dx =I^2$$
Polar Coordinates: $x^2+y^2=R^2,-\pi\leqslant \theta\leqslant +\pi$
$$\int_{-\pi}^{+\pi} \int_{0}^ \infty e^{-(R^2)}\; R\times dR \times d(\theta) =I^2$$
$$2\times \pi \int_{0}^ \infty e^{-(R^2)}\; R\times dR =I^2$$
$$-R^2=P\implies -2Rd(R)=d(P)\implies Rd(R)=-d(P)/2$$
$$2\times \pi \int_{-\infty}^ 0 e^{(P)}d(P)/2$$
$$\pi=I^2\Longrightarrow I=\sqrt{\pi}$$
since $e^{x^2}$ is even $\implies$ ans=${\sqrt{\pi}/2}$

$\endgroup$
  • 3
    $\begingroup$ i was looking for other method than changing into polar coordinate. possibly using infinite series $\endgroup$ – Santosh Linkha Aug 29 '12 at 7:04
  • $\begingroup$ still thank you for your effort!! $\endgroup$ – Santosh Linkha Aug 29 '12 at 7:17
3
$\begingroup$

We use the change of variables $y=x^2$. $$ \int_0^\infty e^{-x^2} \; dx = \frac{1}{2}\int_{0}^{\infty} y^{-1/2} {\rm e}^{-y} \,dy = \frac{1}{2} \Gamma(\frac{1}{2}) \,,$$

where $\Gamma(x)$ is defined by the integral, $$\Gamma( x ) = \int_{0}^{\infty} y^{x-1} {\rm e}^{-y} \,dy \,. $$

Series Method

If you are interested in series method, then you can use Watson's lemma;

$\endgroup$
  • 2
    $\begingroup$ I am suspecting the value of Gamma(1/2) is determined according to normal curve $\endgroup$ – Santosh Linkha Aug 29 '12 at 7:27
  • 1
    $\begingroup$ maybe you should add $\Gamma(1-z) \; \Gamma(z) = {\pi \over \sin{(\pi z)}} \, $. With $z=1/2$ you get $\Gamma^2(1/2)=\pi$... $\endgroup$ – draks ... Aug 29 '12 at 7:31
  • 2
    $\begingroup$ But this does not provide the value of the integral, unless one knows the value of $\Gamma(1/2)$--which is taking the answer for granted, only in a very thinly disguised version. $\endgroup$ – Did Aug 29 '12 at 9:54
1
$\begingroup$

Consider the mapping $\eta\! : \mathbb{R}^2\to \mathbb{R}$ given by $$ \eta((x,y)) = \sqrt{x^2+y^2},\quad (x,y)\in\mathbb{R}^2. $$ (1) Show that the image-measure $\lambda_2\circ\eta^{-1}$ is the measure on $(\mathbb{R},\mathcal{B}(\mathbb{R}))$ with density $$ f(z)=2\pi z 1_{(0,\infty)}(z),\quad z\in\mathbb{R}, $$ by using Dynkin's Lemma.

(2) Show that $$ \int_{\mathbb{R}^2} e^{-x^2-y^2}\,\lambda_2(\mathrm{d}x,\mathrm{d}y)=\pi $$ by using the formula for integration under measureable transformations.

(3) Use Tonelli's theorem to conclude that $$ \int_{\mathbb{R}}e^{-x^2}\,\lambda(\mathrm{d}x)=\sqrt{\pi}, $$ and now your result follows.

$\endgroup$
1
$\begingroup$

First, we notice that

$$n!~=~\int_0^\infty e^{-\sqrt[n]x}~dx\quad\iff\quad\tfrac1n!~=~\int_0^\infty e^{-x^n}dx\quad\rightarrow\quad\tfrac12!~=~\int_0^\infty e^{-x^2}dx.$$

Then, we further notice that

$$\int_0^1\Big(1-\sqrt[n]x\Big)^m~dx~=~\int_0^1\Big(1-\sqrt[m]x\Big)^n~dx~=~\frac1{C_{m+n}^n}~=~\frac1{C_{m+n}^m}~=~\frac{m!~n!}{(m+n)!},$$

from where we ultimately deduce that

$$\frac\pi4~=~\int_0^1\sqrt{1-x^2}~dx~=~\frac{\Big(\frac12!\Big)^2}{\Big(\frac12 + \frac12\Big)!}~=~\Big(\tfrac12!\Big)^2,$$

which, in its turn, leads us to finally conclude that

$$\int_0^\infty e^{-x^2}dx~=~\tfrac12!~=~\sqrt{\pi\over4}~=~\frac{\sqrt\pi}2.$$

Q.E.D.

$\endgroup$
0
$\begingroup$

Let $I=\displaystyle \int_0^{+\infty} e^{-t^2}dt$

Let $f(x)=\displaystyle \int_0^{\tfrac{\pi}{4}} e^{-\tfrac{x^2}{\cos^2t}}dt$

(notice : since $f(x)\leq e^{-x^2}$ then $\lim_{x \rightarrow +\infty}f(x)=0$ )

Let $g(x)=\displaystyle \int_0^x e^{-t^2}dt$

First:

For $x>0$

$\displaystyle x\int_0^{\tfrac{\pi}{4}} \dfrac{e^{-x^2\tan^2 t}}{\cos^2t}dt=g(x)$ (1)

(perform change of variable $u=x\tan t$ )

$\displaystyle-2e^{-x^2}g(x)=-2e^{-x^2}\int_0^x e^{-t^2}dt=-2e^{-x^2}x\int_0^{\tfrac{\pi}{4}} \dfrac{e^{-x^2\tan^2 t}}{\cos^2t}dt$ (using (1))

$\displaystyle-2e^{-x^2}g(x)=-2x\int_0^{\tfrac{\pi}{4}} \dfrac{e^{-x^2(1+\tan^2 t)}}{\cos^2t}dt=-2x\int_0^{\tfrac{\pi}{4}} \dfrac{e^{-\tfrac{x^2}{\cos^2t}}}{\cos^2t}dt=f'(x)$ (2)

$(g(x)^2)'=2e^{-x^2}g(x)=-f'(x)$ (using (2))

Therefore:

$g(x)^2+f(x)$ is constant for all $x$

and $g(0)^2+f(0)=\dfrac{\pi}{4}$

so for all $x$

$g(x)^2+f(x)=\dfrac{\pi}{4}$

take the limit of the left member when $x$ goes to infinity:

$I^2=\dfrac{\pi}{4}$

So $I=\dfrac{\sqrt{\pi}}{2}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.